Response to cardiac resynchronization therapy in elderly patients (≥70 years) and octogenarians. (February 2013) - Verbrugge, Frederik H.; Dupont, Matthias; de, Philippe; Rivero‐Ayerza, Maximo; Van Herendael, Hugo; Vercammen, Jan; Jacobs, Linda; Verhaert, David; Vandervoort, Pieter; Tang, W.H. Wilson; Mullens, Wilfried
<x xml:space="preserve">Abstract</x> Aims Cardiac resynchronization therapy (CRT) leads to reverse ventricular remodelling, improved functional capacity, and better clinical outcome in patients with advanced chronic heart failure, reduced ejection fraction, and evidence of ventricular conduction delay, who are under optimal medical therapy. This study investigated whether these benefits can be extrapolated to older patients, typically not included in randomized clinical trials. Methods and results Consecutive patients who received a CRT device between October 2008 and June 2011, including optimization afterwards in a dedicated clinic, were stratified into 3 pre‐specified groups, according to age: <70 years (n = 76); 70–79 years (n = 95); and ≥80 years (n = 49). Left ventricular remodelling, functional capacity, heart failure hospitalization, and mortality data were assessed during follow‐up. Reverse left ventricular remodelling and improvement in New York Heart Association functional class were similar in all groups at 6 months after implantation. During mean follow‐up of 20 months, 32 patients died and 66 were admitted for heart failure. Annualized mortality rates were significantly higher in elderly patients (6% vs. 8% vs. 15% in all groups, respectively; P < 0.001), but time to death or first heart failure admission was similar among age groups (P = 0.531). Progressive pump failure was the major cause of death (50%), with co‐morbidity‐related deaths also being frequent (41%). Conclusion Reverse left ventricular remodelling and functional capacity improvement after CRT are sustained at advanced age. Moreover, time to all‐cause mortality or heart failure admission was similar, irrespective of age, in a context of maximized optimization including optimal medical therapy.